Model pembelajaran untuk meningkatkan kemampuan emosi dan sosial peserta didik berkebutuhan khusus - Nandi Warnandi (Inovasi Kurikulum, 2015)
There are a number of reasons why the emotional and social abilities of students with special needs in inclusive primary schools are very low, among others, is the fact that the schools have not developed learning models specifically focusing on improving emotional and social abilities. Then, the problem formulated in this research is: "Can TGT (Teams-Games-Tournament) learning model improve the emotional and social abilities of students with special needs in inclusive primary schools, and is TGT learning model better than conventional learning model in improving the emotional and social abilities of students with special needs in inclusive primary schools?" Hence, the research aims to: Produce a learning model that can improve the emotional and social abilities of students with special needs in inclusive primary schools. The research hypothesized: "TGT learning model can improve the emotional and social abilities of students with special needs, and TGT learning model is better than conventional learning model in improving the emotional and social abilities of students with special needs in inclusive primary schools. The method adopted was Research and Development. To meet the research objectives, the researcher employed mixed methods, combining qualitative and quantitative methods with the aim of obtaining answers more appropriate to the research questions. The two types of data in the research are mutually completing, considering both of them are required to strengthen the research findings. The data were then analyzed quantitatively using t-test. The research results show: The learning models used in inclusive primary schools are conventional, showing that there has not been any effort in improving the emotional and social abilities of students with special needs, where they are frequently not involved in teaching and learning, considered as incapable, and positioned at the back of the classroom. The use of TGT model has brought significant impact on the improvement of special needs students' emotional and social abilities, where there were significant increases in the learning outcomes using TGT model that it could be concluded that TGT learning model adjusted to special needs students' condition was suitable to improve their emotional and social needs. Furthermore, TGT model was better than the conventional one in improving the emotional and social abilities of students with special needs in inclusive schools. It was also found that the emotional and social competence of students with special needs in inclusive schools in majority lagged behind students in general. Hence, it is recommended that Directorate of Special Education and Services, Provincial Department of Education, and Regional/Municipal Department of Education create extension programs to disseminate TGT model, while continuing to consider the obstacles faced by students with special needs. The future researchers are expected to broaden the scope of research subjects, so that the research findings will truly represent the special needs students' teaching and learning.